Solid pancreatic masses in children: A review of current evidence and clinical challenges - Patterson, Kelli N.; Trout, Andrew T.; Shenoy, Archana; Abu-El-Haija, Maisam; Nathan, Jaimie D. (Frontiers in Pediatrics, 2022)
Pancreatic tumors in children are infrequently encountered in clinical practice. Their non-specific clinical presentation and overlapping imaging characteristics often make an accurate preoperative diagnosis difficult. Tumors are categorized as epithelial or non-epithelial, with epithelial tumors further classified as tumors of the exocrine or endocrine pancreas. Although both are tumors of the exocrine pancreas, solid pseudopapillary neoplasm is the most prevalent solid pancreatic tumor in children, while pancreatoblastoma is the most common malignant tumor. Insulinoma is the most common pediatric pancreatic tumor of the endocrine pancreas. Malignant tumors require a complete, often radical, surgical resection. However, pancreatic parenchyma-sparing surgical procedures are utilized for benign tumors and low-grade malignancy to preserve gland function. This review will discuss the epidemiology, pathophysiology, clinical and diagnostic characteristics, and management options associated with both common and rare solid pancreatic masses in children. We will also discuss current challenges encountered in their evaluation and treatment.